The Philippine community school - Bernardino, Vitaliano 1908-
This study addressed the need for a comprehensive and thorough treatment of the community school, historically and operationally. It includes the nature and characteristics of the Philippine Community School, its origin, and its aims and objectives. The results of the Philippine Community School have been appraised, its fundamental principles and practices evaluated and its prospects analyzed.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Keywords: Community and school